“Nipahol”: A Locally Formulated Sanitizer/Disinfectant from Nipa Bioethanol for Possible Use Against Covid-19 - Roque A. Ulep; James Paul T. Madigal; Thiara Celine E. Suarez; Karyl Mae D. Ramos; Jayson F. Cariaga; Shirley C. Agrupis (Agro Bali : Agricultural Journal, 2022)
“Nipahol” is high-grade bioethanol produced from nipa sap using the proprietary fermentation and distillation technologies developed by a group of researchers at the Mariano Marcos State University-National Bioenergy Research and Innovation Center (MMSU-NBERIC). To ensure the quality and efficacy of the formulated product, the present study was set to explore the antibacterial potential of the locally formulated nipa disinfectant/antiseptic as an alternative alcohol formulation for possible use during the COVID-19 pandemic using standard microbiological assays. Susceptibility test revealed that at least 70% nipa alcohol formulations showed inhibitory activity against Staphylococcus aureus (6.25 mm and 4.25 mm zone of inhibitions). The 95% nipa alcohol concentration showed a bactericidal effect against Escherichia coli and S. aureus. High percent (%) bacterial cell reduction (90-99.9% log reduction) was observed when alcohol concentration and time increases. A confirmatory antimicrobial susceptibility test conducted by Philippine Department of Science and Technology, Microbiology Division reported that 95% nipa alcohol showed active inhibitory effect to test organisms while partial active observed in 70% nipa alcohol formulation. Glo-Germ Test revealed nipa disinfectant/antiseptic is as effective as commercial alcohol, thus, it can be utilized as an alternative intervention to prevent the spread of infectious microorganisms. The effectiveness of nipa disinfectant/antiseptic formulations is heightened with proper handwashing, strictly following proper hygiene, and health protocols. In conclusion, the formulated nipahol possesses the antibacterial potential to inhibit the multiplication of E. coli and S. aureus.